2012
DOI: 10.2527/jas.2011-4568
|View full text |Cite
|
Sign up to set email alerts
|

ALPHARMA BEEF CATTLE NUTRITION SYMPOSIUM: Implications of nutritional management for beef cow-calf systems1

Abstract: The beef cattle industry relies on the use of high-forage diets to develop replacement females, maintain the cow herd, and sustain stocker operations Forage quantity and quality fluctuate with season and environmental conditions Depending on class and physiological state of the animal, a forage diet may not always meet nutritional requirements, resulting in reduced ADG or BW loss if supplemental nutrients are not provided It is important to understand the consequences of such BW loss and the economics of provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
0
34
0
5
Order By: Relevance
“…Concepts of developmental programming, or the idea that stressors during critical windows of development can have both short- and long-term consequences in offspring, began to emerge about three decades ago based on human epidemiological studies ( Barker, 1992 , 2004 ). Research with animal models, including livestock, has since demonstrated that developmental programming is probably universal and that consequences on offspring growth, development, and health are likely much larger than previously thought ( Wu et al, 2006 ; Caton and Hess, 2010 ; Funston et al, 2012 ; Reynolds and Caton, 2012 ; Greenwood et al, 2017 ; Hoffman et al, 2017 ; Reynolds et al, 2017 ). Maternal stress, particularly nutritional stress, is one of the major drivers of negative consequences of developmental programming in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Concepts of developmental programming, or the idea that stressors during critical windows of development can have both short- and long-term consequences in offspring, began to emerge about three decades ago based on human epidemiological studies ( Barker, 1992 , 2004 ). Research with animal models, including livestock, has since demonstrated that developmental programming is probably universal and that consequences on offspring growth, development, and health are likely much larger than previously thought ( Wu et al, 2006 ; Caton and Hess, 2010 ; Funston et al, 2012 ; Reynolds and Caton, 2012 ; Greenwood et al, 2017 ; Hoffman et al, 2017 ; Reynolds et al, 2017 ). Maternal stress, particularly nutritional stress, is one of the major drivers of negative consequences of developmental programming in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Funston et al (2012a) reported that this feed restriction often prevents cows from presenting adequate body condition score and, consequently, from achieving the required nutritional status for conception. In such cases, feeding strategies using protein supplementation, protein salt, and supplemental Ca salts containing polyunsaturated fatty acids are alternatives to increase body weight and reproductive performance (Lopes et al 2011;Funston et al 2012a;Funston et al 2012b). We found that HWR and IWR farmers offered proteinated salt more frequently than LWR farmers, indicating a better nutrient supply to their herds as shown by the higher weaning rates obtained.…”
Section: Resultsmentioning
confidence: 76%
“…Desta forma, os efeitos da utilização da eCG nas taxas de prenhez/ovulação em vacas Nelore têm sido bastante controversos, tendo em vista que a eficácia deste tratamento tem se limitado a vacas com baixo ECC (Baruselli, Reis et al, 2004), não cíclicas (Baruselli, Marques et al, 2001) e vacas primíparas (Small, Colazo et al, 2009). Foi observada uma relação entre o ECC e as taxas de ovulação e prenhez/IA, porém este efeito se deu de forma independente do tratamento com eCG, confirmando a relação entre a condição nutricional e a eficiência reprodutiva (Diskin, Mackey et al, 2003;Funston, Summers et al, 2011). A ausência de interação entre as variáveis ECC e tratamento com eCG contraria alguns estudos que relataram efeito do tratamento com eCG na indução da ovulação em Bos indicus com baixo ECC (2,5), resultando em maior taxa de prenhez (55,4% vs. 40,7%) (Baruselli, Madureira et al, 2004) o que também ocorreu em Bos taurus (Souza, Viechnieski et al, 2009).…”
Section: Discussionunclassified